Trogophloeus tripunctulatus Coiffait, 1981, a new synonym of Carpelimus insularis (Kraatz, 1858) (Coleoptera: Staphylinidae: Oxytelinae) - Makranczy, György (Zootaxa, 2013)
In the course of a type revision for all the New World members of the very speciose genus Carpelimus Leach, 1819, taxa described from the Galápagos Archipelago were investigated. There were five species described by Coiffait (1981) as Trogophloeus, despite the fact that since 1970 Carpelimus was the valid name of the genus; and descriptions were lacking illustrations. One of these taxa, Trogophloeus (?Boopinus) tripunctulatus Coiffait, 1981: 304 was based on a single, particularly poorly preserved specimen. In this type both antennae are missing (except first two antennomeres on both sides), the forebody appears smashed, the head is split on the left side under the eye, so that the left eye appears much larger than the right one, and the pronotum has cracks (one large across right side of disc, and some smaller ones along anterior edge). The pubescence is present only partially, and the pronotal sculpture may partly be distorted. The elytra are also cracked longitudinally on both sides. Some legs are missing. Describing a new taxon based on such material is unexcusable.